PENGARUH FAKTOR INDIVIDUAL, SITUASIONAL, DAN ORGANISASIONAL TERHADAP NIAT MELAKUKAN WHISTLE-BLOWING PADA AKUNTAN DI BATAM - Rusda Irawati; Mega Mayasari; Adi Irawan (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
This study aims to examine the perceptions of employees of the Accounting Section in Batam related with the influence of individual, situational and organizational factors on the intention to doing internal and external whistle-blowing. The data collection technique used is Purposive sampling. The method used to obtain research data is through a survey with questionnaires. Questionnaires distributed to Student class employees Accounting Study Program and Management Accounting Program Managerial, Batam State Polytechnic working in Accounting Section. The collected questionnaires were analyzed using PLS-SEM. The results of this study indicate that the factors that affect the intentions of employees of Accounting Division to conduct internal whistle-blowing are attitudes toward whistle-blowing, perceptual behavior control and organizational commitment. While the factors that affect the intentions of employees of Accounting Section to conduct external whistle-blowing is the subjective norm.